Honors to Eileithyia at ancient Inatos : the sacred cave at Tsoutsouros, Crete : highlights of the collection - Kanta, Athanasia; Davaras, Kōstēs; Betancourt, Philip P., 1936- (INSTAP Academic Press, 2022)
"In 1962, after secret looting, a shrine for the Greek Goddess Eileithyia was discovered by the police in south-central Crete at the modern town of Tsoutsouros (ancient Inatos). The cave dedicated to this ancient goddess of childbirth and motherhood was excavated that year by Nikolaos Platon and Costis Davaras on behalf of the Archaeological Museum in Herakleion. It was filled with votive gifts including over 100 items of gold along with Egyptian figurines and seal stones, bronze objects, and hundreds of clay figurines. The shrine was use starting before 2000 B.C. and continuing to the Roman Imperial period. Many of the clay images are especially appropriate for this deity because they include pregnant women, embracing couples, figures in preparation for childbirth, mothers holding babies, and a young child in its crib. A Greek language book highlighting the shrine and its major discoveries is now translated into English. It provides images, catalog entries, and explanatory texts for the most important discoveries from this unique shrine"--